2007
DOI: 10.1097/fpc.0b013e32800ffba0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2D6 metabolizer status on the disposition of the (+) and (−) enantiomers of perhexiline in patients with myocardial ischaemia

Abstract: Perhexiline's pharmacokinetics exhibit significant enantioselectivity in CYP2D6 extensive/intermediate and poor metabolizers, with both enantiomers displaying polymorphic and saturable metabolism via CYP2D6. Clinical use of rac-perhexiline may be improved by developing specific enantiomer target plasma concentration ranges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
3
10
0
1
Order By: Relevance
“…The microsomal data from this study unequivocally demonstrate that both enantiomers of PHX are subject to significant polymorphic metabolism by CYP2D6, although this enzyme exhibits distinct stereoselectivity with respect to the conformation of metabolites and the rate at which they are formed, consistent with the enantioselective pharmacokinetics observed in vivo for CYP2D6 EMs (Gould et al, 1986;Inglis et al, 2006). This study is the first…”
Section: Discussionsupporting
confidence: 59%
“…The microsomal data from this study unequivocally demonstrate that both enantiomers of PHX are subject to significant polymorphic metabolism by CYP2D6, although this enzyme exhibits distinct stereoselectivity with respect to the conformation of metabolites and the rate at which they are formed, consistent with the enantioselective pharmacokinetics observed in vivo for CYP2D6 EMs (Gould et al, 1986;Inglis et al, 2006). This study is the first…”
Section: Discussionsupporting
confidence: 59%
“…This study confirmed that the female DA rat displays perhexiline pharmacokinetics similar to those in humans, with the chosen dosage regimen attaining plasma perhexiline concentrations that approximate the mid to high range of therapeutic concentrations (0.15‐0.60 mg/L). Similar to humans, we report enantioselective plasma pharmacokinetics of perhexiline in female DA rats, consistent with a greater apparent oral clearance of the (−)‐enantiomer. Furthermore, similar to human CYP2D6 extensive / intermediate metabolisers, the dominant metabolite in plasma following administration of the racemate was cis ‐OH‐perhexiline.…”
Section: Discussionsupporting
confidence: 73%
“…Since the apparent oral clearance of each enantiomer in DA rats was unaffected by the dosage form administered (enantiomer or racemate), and the plasma protein binding of perhexiline is not enantioselective, the steady‐state tissue:plasma concentration ratios should reflect the net tissue uptake of each enantiomer (i.e., the balance between uptake into and elimination from tissue). Therefore, our observations suggest enantioselectivity in the net‐uptake (or tissue binding) of the pure enantiomers, favouring (+)‐perhexiline (2.5‐ to 4.5‐fold greater).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So musste auch der Kalziumantagonist Perhexilin wegen des gehäuften Auftretens von Neuropathien vom Markt genommen werden, Perhexilin ist wie Debrisoquin und Spartein Substrat von CYP2D6, sodass auch in diesem Fall bei Langsammetabolisierern signifikant hö-here Perhexilinplasmakonzentrationen im Vergleich zu schnellen Metabolisierern auftraten [4]. Die Pharmakokinetik von Arzneimitteln wird durch eine Reihe von überwiegend in der Leber exprimierten polymorphen Enzymen beeinflusst.…”
Section: Historischer Hintergrundunclassified